Administration of FTY720 during Tourniquet-Induced Limb Ischemia Reperfusion Injury Attenuates Systemic Inflammation - Foster, Anthony D.; Vicente, Diego; Sexton, Jonathan J.; Johnston, Luke; Clark, Nick; Leonhardt, Crystal; Elster, Eric A.; Davis, Thomas A.; Bradley, Matthew J. (Mediators of Inflammation, 2017)
Acute ischemia-reperfusion injury (IRI) of the extremities leads to local and systemic inflammatory changes which can hinder limb function and can be life threatening. This study examined whether the administration of the T-cell sequestration agent, FTY720, following hind limb tourniquet-induced skeletal muscle IRI in a rat model would attenuate systemic inflammation and multiple end organ injury. Sprague-Dawley rats were subjected to 1 hr of ischemia via application of a rubber band tourniquet. Animals were randomized to receive an intravenous bolus of either vehicle control or FTY720 15 min after band placement. Rats (n=10/time point) were euthanized at 6, 24, and 72 hr post-IRI. Peripheral blood as well as lung, liver, kidney, and ischemic muscle tissue was analyzed and compared between groups. FTY720 treatment markedly decreased the number of peripheral blood T cells (p<0.05) resulting in a decreased systemic inflammatory response and lower serum creatinine levels and had a modest but significant effect in decreasing the transcription of injury-associated target genes in multiple end organs. These findings suggest that early intervention with FTY720 may benefit the treatment of IRI of the limb. Further preclinical studies are necessary to characterize the short-term and long-term beneficial effects of FTY720 following tourniquet-induced IRI.